Neuronal calcium sensor-1 enhancement of InsP3 receptor activity is inhibited by therapeutic levels of lithium - Schlecker, Christina; Boehmerle, Wolfgang; Jeromin, Andreas; DeGray, Brenda; Varshney, Anurag; Sharma, Yogendra; Szigeti-Buck, Klara; Ehrlich, Barbara E. (The Journal of Clinical Investigation, 2006)
Regulation and dysregulation of intracellular calcium (Ca2+) signaling via the inositol 1,4,5-trisphosphate receptor (InsP3R) has been linked to many cellular processes and pathological conditions. In the present study, addition of neuronal calcium sensor-1 (NCS-1), a high-affinity, low-capacity, calcium-binding protein, to purified InsP3R type 1 (InsP3R1) increased the channel activity in both a calcium-dependent and -independent manner. In intact cells, enhanced expression of NCS-1 resulted in increased intracellular calcium release upon stimulation of the phosphoinositide signaling pathway. To determine whether InsP3R1/NCS-1 interaction could be functionally relevant in bipolar disorders, conditions in which NCS-1 is highly expressed, we tested the effect of lithium, a salt widely used for treatment of bipolar disorders. Lithium inhibited the enhancing effect of NCS-1 on InsP3R1 function, suggesting that InsP3R1/NCS-1 interaction is an essential component of the pathomechanism of bipolar disorder.